SELF-SUFFICIENCY OF THE TURKISH AQUACULTURE SECTOR AND FORECASTING ITS PRODUCTION WITH THE ARIMA (BOX-JENKINS) MODEL - Asli DALGIC; Deniz SARICA; Vecdi DEMIRCAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
With its seas and water resources, Türkiye’s aquaculture industry plays a significant role in both the nation’s economy and society’s ability to eat healthily. The objectives of this study are to evaluate the level of self-sufficiency in aquaculture production, assess the developments in the aquaculture sector in Türkiye, and estimate the production amount for the next ten years employing the ARIMA (Autoregressive Integrated Moving Average) method using the aquaculture production amounts between 1950 and 2021. Making forecasts for the upcoming years is believed to be beneficial in terms of investment and production planning. The amount of aquaculture production was estimated with the Box-Jenkins ARIMA method. As a result of the analyses performed, the ARIMA (1, 2, 2) model was found to be the most suitable model for forecasting aquaculture production. According to the estimation, it is expected to increase by 17.29% between 2022 and 2031. It is believed that depending on this rise, actions should be taken to expand the aquaculture processing facilities associated with the aquaculture sector.